Ultrathin Transition Metal Dichalcogenide/3d Metal Hydroxide Hybridized Nanosheets to Enhance Hydrogen Evolution Activity - Zhu, Zhengju; Yin, Huajie; He, Chun‐Ting; Al‐Mamun, Mohammad; Liu, Porun; Jiang, Lixue; Zhao, Yong; Wang, Yun; Yang, Hua‐Gui; Tang, Zhiyong; Wang, Dan; Chen, Xiao‐Ming; et al. (Advanced materials (Weinheim), 2018)
The vast majority of the reported hydrogen evolution reaction (HER) electrocatalysts perform poorly under alkaline conditions due to the sluggish water dissociation kinetics. Herein, a hybridization catalyst construction concept is presented to dramatically enhance the alkaline HER activities of catalysts based on 2D transition metal dichalcogenides (TMDs) (MoS2 and WS2). A series of ultrathin 2D‐hybrids are synthesized via facile controllable growth of 3d metal (Ni, Co, Fe, Mn) hydroxides on the monolayer 2D‐TMD nanosheets. The resultant Ni(OH)2 and Co(OH)2 hybridized ultrathin MoS2 and WS2 nanosheet catalysts exhibit significantly enhanced alkaline HER activity and stability compared to their bare counterparts. The 2D‐MoS2/Co(OH)2 hybrid achieves an extremely low overpotential of ≈128 mV at 10 mA cm−2 in 1 m KOH. The combined theoretical and experimental studies confirm that the formation of the heterostructured boundaries by suitable hybridization of the TMD and 3d metal hydroxides is responsible for the improved alkaline HER activities because of the enhanced water dissociation step and lowers the corresponding kinetic energy barrier by the hybridized 3d metal hydroxides. Ultrathin 2D hybrids are designed and prepared via surface modification of monolayer MoS2 and WS2 nanosheets by metal (Ni, Co, Fe, Mn) hydroxides, which form a new class of alkaline hydrogen evolution reaction (HER) electrocatalysts. The surface introduction of metal hydroxides can effectively reduce the kinetic barrier of the prior water dissociation step of the alkaline HER reaction.